Derecho del mar en Colombia, conflicto limitrofe entre Colombia y Venezuela. Una posibilidad de crisis de la soberanía Colombiana (2014)
Sovereignty as principal for statehood element should radiate all territorial dimensions, which is why the Law of the Sea is a legal institution that should regulate the limits of the States in maritime areas. However, sometimes, as in the case of dispute between Colombia and Venezuela, where are unclear border areas, it is clear that in the absence of an international instrument or bilateral, is perhaps threatens national sovereignty of any of both countries